2023
DOI: 10.21315/mjms2023.30.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Dance Exercise and Honey Supplementation Followed by Their Subsequent Cessation on Bone Metabolism Markers and Antioxidant Status in Young Collegiate Females

Abstract: Background: Regular physical activity and proper nutritional intake are crucial for bone health. However, it is unclear if this health benefit is maintained after the removal of these stimuli. This study investigated the combined effects of aerobic dance exercise and honey supplementation, followed by their subsequent cessation on bone metabolism markers and antioxidant status in females. Methods: Forty-eight young female college students were assigned into four groups: i) 16S (16 weeks of sedentary activity)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The idea that bee products contain antioxidant properties is supported by a study conducted on mice reporting that honey intervention at doses of 4.6 and 9.2 g/kg for 7 days followed by lipopolysaccharide induction had the potential to reduce the production of reactive oxygen species (ROS) (Ranneh et al, 2021). In addition, a study conducted on young women reported that honey supplementation given at a dose of 20 g and dissolved in 300 mL water during aerobic exercise was effectively able to maintain bone health and antioxidant status triggered by exercise (Tavafzadeh et al, 2023). Furthermore, the results of this study were strengthened by research which reported that swimmers who were given bee product intervention in the form of royal jelly supplementation at a dose of 400 mg for 10 days had the potential to reduce oxidative stress and speed up recovery after training (Ovchinnikov et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that bee products contain antioxidant properties is supported by a study conducted on mice reporting that honey intervention at doses of 4.6 and 9.2 g/kg for 7 days followed by lipopolysaccharide induction had the potential to reduce the production of reactive oxygen species (ROS) (Ranneh et al, 2021). In addition, a study conducted on young women reported that honey supplementation given at a dose of 20 g and dissolved in 300 mL water during aerobic exercise was effectively able to maintain bone health and antioxidant status triggered by exercise (Tavafzadeh et al, 2023). Furthermore, the results of this study were strengthened by research which reported that swimmers who were given bee product intervention in the form of royal jelly supplementation at a dose of 400 mg for 10 days had the potential to reduce oxidative stress and speed up recovery after training (Ovchinnikov et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a randomized controlled trial on 79 healthy postmenopausal women failed to demonstrate any difference in bone density after 4 months of 20 g daily supplementation of honey versus hormonal replacement therapy, but the study was limited by the small sample size and short duration, as changes in bone mass usually occur at a slow rate [ 152 ]. Three different studies investigated the effects of combined aerobic dance exercise and honey supplementation [ 153 , 154 , 155 ]. The first was conducted on young women: the combined aerobic dance exercise and supplement of 20 g/day honey showed the greatest effect in increasing serum BALP levels compared to the honey supplement or aerobic exercise alone [ 153 ].…”
Section: Functional Foods With Impact On Healthmentioning
confidence: 99%
“…The first was conducted on young women: the combined aerobic dance exercise and supplement of 20 g/day honey showed the greatest effect in increasing serum BALP levels compared to the honey supplement or aerobic exercise alone [ 153 ]. In another study on 46 young women, after 8 weeks of daily supplementation of 20 g honey and dance exercise, the highest increase in mean serum BALP and osteocalcin concentrations was observed, with a significant reduction in CTX serum levels [ 154 ]. In older women aged 25 to 40 years old, daily supplementation of 20 g honey for 8 weeks elevated serum total calcium level, whereas aerobic dance sessions alone increased cross-linked carboxyterminal telopeptide of type I collagen (1CTP).…”
Section: Functional Foods With Impact On Healthmentioning
confidence: 99%